Pengaruh saving motives, kompetensi dan pengalaman positif terhadap keputusan membeli asuransi dengan kecenderungan membeli sebagai variabel mediasi - Kristina Mersis; Mellyza Silvi (STIE Perbanas Surabaya, 2019)
The aim of this study was to examine the effect of saving motives, competency, and positive experience on insurance purchasing decision with the intention to purchase as a mediating variable. The study took 295 respondents which were taken based on the criteria such as having insurance and being a decision maker to buy insurance and living in Surabaya, Gresik, and Tuban. The data were analyzed using a Partial Least Square Structural Equation Modeling (PLS-SEM) by using PLS 6.0 program. The results showed that saving motives, competency and positive experience have a significant positive effect on insurance purchasing decision, while the inclination to purchase can mediate the effect of competency and positive experience on insurance purchasing decision.